Performance evaluation of a 3-priority based Mixed Priority Queueing (MPQ) policy with application to input and output queueing ATM switch - Mohd Ali, Borhanuddin; Abbas, Mazlan; Ahmed, Sohail; Moorehead, Donovon
We propose a Mixed Priority Queueing (MPQ) model to improve the Quality Of Service (QOS) for 3 different classes of traffic in ATM switch. In this paper, a single stage input and output buffered nonblocking ATM switch is considered. In order to resolve a certain degree of external conflicts at the output ports, the switching fabric allows limited queueing at the output ports incorporating output buffers of suitable size. The problem of overflow at the output buffers is solved by placing rejected cells in the input port buffers. The MPQ scheme is implemented as a buffer management scheme on the input and output port buffers of the switch. Using computer simulation under both uniform and bursty traffic, the paper analyzes the throughput, delay and cell loss probability (CLP) for the each class of traffic with a variety of traffic loads and switching sizes. It is shown that the performance of the ATM switch increases in terms of throughput, delay and Cell Loss Probability (CLP).